Community Structure of Molluscs at Batu Kijuk Village - Dining Aidil Candri; Laela Junnita Hidayati; Hilman Ahyadi; Yuliadi Zamroni (Postgraduate, University of Mataram, 2023)
Batu Kijuk Beach is one of the coastal areas located in West Nusa Tenggara. Its territory used for a tourist attraction and crossing to Gili Nanggu, Gili Gede and Gili Kedis. These coastal have a wealth of marine life, one of them is mollusc. This study aims to analyze the structure of mollusk community using the Systematic Plot Sampling method. This research was conducted in June-September 2019 in Batu Kijuk, Sekotong District, West Lombok, NTB. Identification and data analysis was carried out at the Marine Biology Laboratory, University of Mataram. From the results of research with 10 transects and 70 quadrants, there are 79 species with a total of 927 species of molluscs. The gastropod class consists of 65 species and 14 species of bivalves. The most common types of species found were from the family Columbellidae with 262 species, nassaridae 109 individuals, strombidae 82 species, cypraeidae 58 species and the rest were found 1-15 species. From the results of data analysis calculations, it was obtained that the highest abundance was Pyrene versicolor (3.70 Ind/m2), Nassaridae which was dominated by Hebra nigra with 2.91 (Ind/M2) and Nassarius globosus had an abundance value of 1.08 (Ind/m2). The index value of diversity (H') for molluscs in Batu Kijuk coastal is included in the high category, 2.74. The dominance index value (C) is 0.1 which means that no mollusk species dominates. The uniformity index (E) has a value of 0.62 which means moderate uniformity because only a few species dominate so that the community can be said to be quite stable.